2002
DOI: 10.1111/j.0014-3820.2002.tb01467.x
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Consequences of the Genealogical Species Concept

Abstract: Abstract.A genealogical species is defined as a basal group of organisms whose members are all more closely related to each other than they are to any organisms outside the group (''exclusivity''), and which contains no exclusive group within it. In practice, a pair of species is so defined when phylogenies of alleles from a sample of loci shows them to be reciprocally monophyletic at all or some specified fraction of the loci. We investigate the length of time it takes to attain this status when an ancestral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
386
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 471 publications
(404 citation statements)
references
References 42 publications
16
386
0
2
Order By: Relevance
“…Briefly, because the three genes are evolving independently, and may not always accurately reflect the history of the species' relationships, we used the gene trees to search for the 'best-fit' species tree that minimizes the number of deep coalescences of the gene trees (Maddison 1997). Gene trees of recently diverged taxa may not be monophyletic, due to incomplete lineage sorting (Hudson & Coyne 2002;Funk & Omland 2003), although a significant phylogenetic signal may still be present (Maddison & Knowles 2006). By accounting for the possibility of incomplete lineage sorting, this approach infers of species' relationships without requiring the gene trees to be monophyletic.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, because the three genes are evolving independently, and may not always accurately reflect the history of the species' relationships, we used the gene trees to search for the 'best-fit' species tree that minimizes the number of deep coalescences of the gene trees (Maddison 1997). Gene trees of recently diverged taxa may not be monophyletic, due to incomplete lineage sorting (Hudson & Coyne 2002;Funk & Omland 2003), although a significant phylogenetic signal may still be present (Maddison & Knowles 2006). By accounting for the possibility of incomplete lineage sorting, this approach infers of species' relationships without requiring the gene trees to be monophyletic.…”
Section: Methodsmentioning
confidence: 99%
“…The estimates of divergence time between the four species show that P. breweriana separates from the others, whereas P. glauca was more closely related to P. abies than to P. mariana. Phylogenetic relationship based on organelle DNA could be unreliable because of higher rate of random genetic drift rate and complete linkage among loci, making mitochondrial DNA in essence equivalent to a single locus (Hudson and Coyne, 2002). Thus, we randomly picked out one individual in each species and constructed a phylogenetic tree based on multi-locus nuclear DNA using BEST programme (Liu and Pearl, 2007).…”
Section: Polymorphism At Allozyme and Nucleotide Levelsmentioning
confidence: 99%
“…Actually, recent genomic studies have largely confirmed its importance for recent speciation events (for example, Patterson et al, 2006). More generally, Hudson and Coyne (2002) have shown that under a simple allopatric model of speciation with no selection it will take approximately 9-12 N e generations for the genealogies of 495% of the loci to be reciprocally monophyletic.…”
Section: Introductionmentioning
confidence: 99%
“…For the COX1 DNA barcode to work under neutral theory, there must be sufficient time for lineages to sort via random accumulation of neutral mutations (Hudson and Coyne 2002) and gene flow among species must be negligible (Lohse 2009). In birds, however, huge radiations of species with unique COX1 nucleotide sequences evolved within a time period significantly less than the time required for complete lineage sorting under neutral theory.…”
Section: Introductionmentioning
confidence: 99%